“The stony heart”: perioperative management of severe mitral annular calcification and porcelain left atrium in a patient requiring prolonged cardiopulmonary bypass - Ramachandran, Sangaraamunisen; Francis, Thomas; Jasid, Abdul M. B. (International Surgery Journal, 2026)
Mitral annular calcification (MAC) presents a formidable challenge in cardiac surgery, often transforming routine valve replacement into a complex reconstruction. When combined with a "porcelain" left atrium, the risks of atrioventricular disruption and inability to expose the valve increase exponentially. Herein this case report presents the case of a 56-year-old female with rheumatic heart disease and a "porcelain" left atrium who underwent mitral valve replacement (MVR). Preoperative multidisciplinary discussion, including consultation with visiting US cardiothoracic faculty, established a consensus to "respect the calcium" rather than perform radical debridement, prioritizing atrioventricular integrity over annular geometry. The intraoperative course was complicated by a rigid, calcified annulus resulting in significant paravalvular leak (PVL). This necessitated two surgical revisions and a total cardiopulmonary bypass time of 367 minutes. Following a managed recovery strategy, the patient was extubated on postoperative day 2 and discharged home on day 7. Severe MAC with a porcelain atrium represents a "double jeopardy" scenario. Successful management requires a multidisciplinary "respect the calcium" strategy and the mandatory use of intraoperative transesophageal echocardiography (TOE). This case demonstrates that prolonged bypass time is a justifiable investment to ensure a competent valve and that aggressive ICU management can mitigate the physiological insult of extended surgery.